Hukum Idah Perceraian bagi Wanita Hamil Akibat Perbuatan Zina - Rahmat, Rahmat; Indriani, Sri (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
Marriage and divorce of women who have become pregnant as a result of adultery are problems that are given attention in the discussion of Islamic jurisprudence. Marrying a pregnant woman due to adultery has been a polemic among Islamic scholars since long ago in various countries, including in Indonesia until it was finally stipulated in the Book of Compilation of Islamic Law which became an explanation of the Law on Marriage. Divorce after marriage, which is preceded by pregnancy due to adultery, is also an interesting discussion, especially regarding the issue of idah, or the waiting period for women who are pregnant and subject to divorce. Idah or waiting period has been prescribed by Islam for the noble purpose of maintaining the authenticity of one's lineage so as not to mix with others. This problem was studied from a socio-cultural normative perspective, which compares the arguments and factual conditions, thus giving different values. Law of idah can differ from one woman to another, based on the type of divorce or the process of breaking the marriage bond, as well as on the woman's condition. The law of divorce for women who are pregnant that is the birth of the child they are carrying can also apply to women who are divorced, while they are pregnant as a result of adultery.